Skin Rash with Acute Respiratory Distress Syndrome in Chronic Miliary Tuberculosis: The Role of HRCT Thorax and Bronchoscopy as Diagnostic Tools - Priyanka Malhotra; Mahesh Unni; Abhishek Vairagade; Patil Shital (The Journal of Association of Chest Physicians)
Pulmonary tuberculosis (TB) is a leading cause of mortality and morbidity in India, presenting with diverse clinical and radiological manifestations such as consolidation, cavitation, lymphadenopathy, pleural effusion, miliary TB, and endobronchial TB. While acute miliary TB presenting as Acute respiratory distress syndrome (ARDS) is documented, the association with a skin rash mimicking viral exanthematous fever is not. This case report describes the case of a 41-year-old male patient with acute dyspnea, a maculopapular rash, and lung infiltrates on chest radiograph, initially diagnosed with acute hypoxic respiratory failure and later confirmed as ARDS. High-resolution computed tomography (HRCT) thorax revealed consolidation with nodules and a characteristic butterfly pattern sparing the apices and bases. Bronchoscopy confirmed TB etiology through MTB genome in BAL samples. The patient improved significantly with intravenous antibiotics, steroids, and HFNC, leading to a documented cure after 6 months of anti-tuberculosis treatment. This report highlights the importance of considering TB in cases with nodular consolidation and positive limiting signs and recommends ICU bronchoscopy as a reliable diagnostic tool. The Kigali modification for ARDS definition was instrumental in managing this case. Use of Kigali modification for defining ARDS in resource limited setting guided management in our case.